1997
DOI: 10.1073/pnas.94.21.11589
|View full text |Cite
|
Sign up to set email alerts
|

Decreased blood pressure response in mice deficient of the α 1b -adrenergic receptor

Abstract: To investigate the functional role of different ␣ 1 -adrenergic receptor (␣ 1 -AR) subtypes in vivo, we have applied a gene targeting approach to create a mouse model lacking the ␣ 1b -AR (␣ 1b ؊͞؊). Reverse transcription-PCR and ligand binding studies were combined to elucidate the expression of the ␣ 1 -AR subtypes in various tissues of ␣ 1b ؉͞؉ and ؊͞؊ mice. Total ␣ 1 -AR sites were decreased by 98% in liver, 74% in heart, and 42% in cerebral cortex of the ␣ 1b ؊͞؊ as compared with ؉͞؉ mice. Because of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
222
3
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(243 citation statements)
references
References 26 publications
12
222
3
2
Order By: Relevance
“…The AR-a 1 can be further classified into AR-a 1A , AR-a 1B and AR-a 1D subtypes with AR-a 1B is found to be dominant in the myocardium of mice. 23,24 Wang et al 25 reported that cardiac expression of constitutively active AR-a 1B is detrimental in terms of cardiac hypertrophy and dysfunction after pressure overload and also that increased AR-a 1A mRNA expression is not a feature of the hypertrophic response to hypertension. Vecchione et al 26 found no occurrence of high blood pressure and LV remodeling in response to noradrenaline stimulation in AR-a 1B À/À mice.…”
Section: Discussionmentioning
confidence: 99%
“…The AR-a 1 can be further classified into AR-a 1A , AR-a 1B and AR-a 1D subtypes with AR-a 1B is found to be dominant in the myocardium of mice. 23,24 Wang et al 25 reported that cardiac expression of constitutively active AR-a 1B is detrimental in terms of cardiac hypertrophy and dysfunction after pressure overload and also that increased AR-a 1A mRNA expression is not a feature of the hypertrophic response to hypertension. Vecchione et al 26 found no occurrence of high blood pressure and LV remodeling in response to noradrenaline stimulation in AR-a 1B À/À mice.…”
Section: Discussionmentioning
confidence: 99%
“…An a 1B -receptor deficient mouse strain had been generated (Cavalli et al, 1997) and had been reported to show 'normal' activity in a novel chamber or open field (Spreng et al, 2001); however, a second group did report a significant reduction in the open field activity with this strain (Knauber and Muller, 2000). In order to determine if there was compensation for the loss of the a 1B -receptor in the mutant mice, we challenged them with large doses of the stimulant, modafinil.…”
Section: Role Of a 1 -Adrenoceptors In Behavioral Activitymentioning
confidence: 99%
“…The three a 1 -AR subtypes (a 1A , a 1B , a 1D ) have been classified via molecular cloning (Cotecchia et al 1988;Lomasney et al 1991;Perez et al 1991;Perez et al 1994). The most well characterized cardiovascular functions associated with a 1 AR stimulation include the contraction and growth of vascular smooth muscle cells and their regulation of blood pressure (Chen et al 1995;Leech and Faber 1996;Cavalli et al 1997;Hrometz et al 1999). In other a 1 AR-expressing tissues such as liver, kidney and heart, the receptors regulate metabolic processes (Kunos and Ishac 1987), sodium re-absorption (Jeffries and Pettinger 1989) and inotropy (Anyukovsky and Rosen 1991), respectively.…”
mentioning
confidence: 99%